EFEKTIFITAS PRODUKSI SAWI CAISIM PADA BERBAGAI MEDIA TANAM - Rizki, Sekar Dwi; Raharjo, Ismadi; Putri, Vera Chania (AGROTEKSOS, 2023)
ABSTRACT   Caisim plants or mustard greens are plants with high nutritional content, used as ingredients for consumpting vegetables and medicines. The Consumption of caisim plants in Indonesia is quite large and evenly distributed throughout the region. This research aims to obtain a good planting media for development of caisim production. The planting media used in this study were soil, cocopeat , husk charcoal, and sand. Planting media was used to represent soil conditions in Indonesia. The research was carried out by planting caisim plants in polybag s with drip irrigation systems and measurements on the 10th, 17th, 24th, and 31st days. The planting medium responds to the growth of caisim plants where the variable height of the planting media which influences the most sequentially is soil, cocopeat , husk charcoal, and sand. For the variable number of leaves in the planting medium it has no effect, but on the growth of leaf width and visually on the soil and cocopeat planting media the leaves grow wide and healthy, the rice husk charcoal planting medium is healthy but small, while the leaves on the sand planting medium tend to be small and wrinkled. This is due to the ability of the planting media to store nutrients and supply caisim plants. Increasing the effectiveness of caisim production at the household scale takes into account the factors of cropping patterns, narrow land use, and provision of irrigation water.